The body musculature of Arthrodire Placoderms - Ahlberg, P.; Trinajstic, Kate; Long, J. (The Palaeontology Association, 2009)
The exceptionally preserved Late Devonian (Frasnian) fishes from the Gogo Formation, Western Australia, have recently been recognized to contain, sometimes extensive, remains of musculature preserved in three dimensions. Mapping of preserved muscles in multiple specimens of two closely related arthrodire placoderms, Compagopiscis and Incisoscutum, enable us to present the first partial map of the body musculature in a stem-group jawed vertebrate. In addition to the expected trunk and tail musculature of segmentally arranged myomeres, these placoderms show two areas of specialized muscular development. Dorsally, extending posteriorly from the rear margin of the skull roof across the nuchal gap and in under the median dorsal plate, are a pair of large muscles that contact each other in the midline and are flanked by a pair of smaller but otherwise similar muscles.These muscles, evidently modifications of the epaxial trunk musculature, must be the head elevators that rotated the head dorsally relative to the trunk armor. Ventrally, the posterior part of the abdominal musculature shows surprising complexity. Ventral to the ends of the segmental myomeres, an elongate, longitudinal, sharply defined belt of obliquely transverse muscle fibers without segmental arrangement extends along most of the length of the posteroventrolateral plate towards (and possibly reaching) the pelvis. Functionally, this may be linked to movement of the pelvic fin, erection of the clasper (in the male), and/or modulation of the movement of the tail base relative to the trunk armor during swimming. Developmentally, the arrangement of these muscle fibers at approximate right angles to the myomeric muscles suggests that they lie ventral to the "lateral somitic frontier", within the zone (also occupied by paired appendages) where muscles are repatterned by an interaction between somatic and lateral plate mesoderm. This is the first direct evidence for such muscles in a stem gnathostome.